Clinicopathologic Features and Calcium Deposition Patterns in Calciphylaxis: Comparison With Gangrene, Peripheral Artery Disease, Chronic Stasis, and Thrombotic Vasculopathy. (September 2019) - McMullen, Emily R.; Harms, Paul W.; Lowe, Lori; Fullen, Douglas R.; Chan, May P.
Abstract : Diagnosis of calciphylaxis is crucial, yet its distinction from other vascular diseases can be challenging. Although vascular calcification and thrombosis are hallmarks of calciphylaxis, the incidence and patterns of these features in other vascular diseases have not been well characterized. The specificity of fine calcium deposits in vessel walls (identifiable on von Kossa [VK] stain only) and other extravascular calcifications is not entirely clear. We retrospectively examined the clinicopathologic features in calciphylaxis (n=27), gangrene and viable skin at amputation margin (n=20 each), chronic stasis (n=22), and thrombotic vasculopathy (n=19) to identify useful discriminators. Calcification of subcutaneous small vessels appreciable on hematoxylin and eosin stain was relatively specific for calciphylaxis, although sensitivity was low (56%). VK detected fine calcium deposits in vessel walls not appreciable on hematoxylin and eosin, however, specificity was limited by frequent finding of similar deposits in peripheral artery disease. Combining calcium deposits detected by VK and thrombosis of subcutaneous small vessels resulted in optimal sensitivity (85%) and specificity (88%) for calciphylaxis. Similar observations applied to medium-sized vessel calcification. Calcification of eccrine gland basement membranes, elastic fibers, and perineurium did not effectively distinguish calciphylaxis from other groups. Diffuse dermal angiomatosis was exclusively found in calciphylaxis in this study. In conclusion, VK is useful in enhancing the detection of vascular calcification and avoiding the false-negative diagnosis, but this finding requires concomitant subcutaneous small vessel thrombosis to support a diagnosis of calciphylaxis. Diffuse dermal angiomatosis should increase suspicion for underlying calciphylaxis and prompt deeper sampling in the appropriate clinical setting.